Kapang Kontaminan Pada Ikan Toreh (Hyporhamphus affinis) yang dijual di Pasar Tradisional Kota Ternate Maluku Utara - Nurhasanah Nurhasanah; Sundari Sundari (Biogenesis: Jurnal Ilmiah Biologi, 2018)
Dried fish from fish Julung (Hyporhamphus affinis) is one type of fish food products that are found in the traditional market of Ternate city. This product is commonly known as fish toreh. The main problem of this product is storage packaging by using an open bamboo set that can be contaminated by various microbes. The purpose of this study was to inventory and identification of contaminant molds isolated from dried fish of H. affinis on a 17-day storage period. The research was conducted in Mathematic and Natural Science laboratory by using dried fish smoke (toreh) from H. affinis obtained from traditional market in Ternate city. Isolation and identification of molds using standard microbiological procedures. Media growth of mold using Potato Dextrose Agar (PDA). Several genus and species of mold found as contaminant mold are Aspergillus spp., Eurotium spp., Torula spp., Cladosporium spp., Polypaecilum pisce and Catenaria fuliginea.